Clinical pharmacokinetic and in vitro combination studies of nolatrexed dihydrochloride (AG337, Thymitaq(TM)) and paclitaxel - Hughes, A N (Nature Publishing Group, 2000)
A clinical study of nolatrexed dihydrochloride (AG337, Thymitaq(TM)) in combination with paclitaxel was performed. The aims were to optimize the schedule of administration and determine any pharmacokinetic (PK) interactions between the two drugs. In vitro combination studies were performed to assist with schedule optimization. Three patients were entered on each of three different schedules of administration of the two drugs: (1) paclitaxel 0–3 h, nolatrexed 24–144 h; (2) nolatrexed 0–120 h, paclitaxel 48–51 h; (3) nolatrexed 0–120 h, paclitaxel 126–129 h. Paclitaxel was administered at a dose of 80 mg m(−2)over 3 h and nolatrexed at a dose of 500 mg m(−2)day(−1)as a 120-h continuous intravenous infusion. Plasma concentrations of both drugs were determined by high performance liquid chromatography. In vitro growth inhibition studies using corresponding schedules were performed using two head and neck cancer cell lines. In both HNX14C and HNX22B cell lines, synergistic growth inhibition was observed on schedule 2, whereas schedules 1 and 3 demonstrated antagonistic effects. In the clinical study, there was no effect of schedule on the pharmacokinetics of nolatrexed. However, patients on schedules 1 and 3 had a higher clearance of paclitaxel (322–520 ml min(−1)m(−2)) than those on schedule 2 (165–238 ml min(−1)m(−2)). Peak plasma concentrations (1.66–1.93 vs 0.86–1.32 μM) and areas under the curve (392–565 vs 180–291 μM min(−1)) of paclitaxel were correspondingly higher on schedule 2. The pharmacokinetic interaction was confirmed by studies with human liver microsomes, nolatrexed being an inhibitor of the major routes of metabolism of paclitaxel. Toxicity was not schedule-dependent. Nolatrexed and paclitaxel may be safely given together when administered sequentially at the doses used in this study. Studies in vitro suggest some synergy, however, due to a pharmacokinetic interaction, paclitaxel doses should be reduced when administered during nolatrexed infusion. © 2000 Cancer Research Campaign